2015
DOI: 10.21608/maj.2015.4632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Un-live Microalgal diet, Nannochloropsis oculata and Arthrospira (Spirulina) platensis, Comparing to Yeast on Population of Rotifer, Brachionus plicatilis

Abstract: Rotifers Brachionus plicatilis are the most common zooplankton used to rear eairly larvae of marine shrimp and finfish. Reduce production cost of live food in marine hatcheries is considered one of the main targets for developing a marine aquaculture industry. The present study is conducted to investigate the population (as increase in number) and population growth rate of rotifer Brachionus plicatilis fed on un-live microalgal diet, frozen Nannochloropsis oculata (FN) and dried Spirulina platensis (DS), compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Also, the various factors may be interdependent and a parameter that is optimal for one set of conditions is not necessarily optimal for another (FAO, 1996). Many studies were conducted in the fields of culture of Egyptian native isolated microalgal species with different environmental conditions (Abdel Rahman et al, 2008;El-Kassas and El-Sheekh, 2016;Abomohra et al, 2014), nutrient limitation (Ashour and Kamel, 2017; Kamil, 2009;Madkour et al, 2012;Nour et al, 2017Nour et al, , 2015aNour et al, and 2015b and even as aquaculture live food (Abdel Rahman et al, 2008 and2010;and El-Wazzan et al, 2009), or as aquaculture powder (Heneash et al, 2016) or as a source of biodiesel (Ashour et al, 2019;Ashour, 2015).…”
Section: Keys Of Microalgae Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the various factors may be interdependent and a parameter that is optimal for one set of conditions is not necessarily optimal for another (FAO, 1996). Many studies were conducted in the fields of culture of Egyptian native isolated microalgal species with different environmental conditions (Abdel Rahman et al, 2008;El-Kassas and El-Sheekh, 2016;Abomohra et al, 2014), nutrient limitation (Ashour and Kamel, 2017; Kamil, 2009;Madkour et al, 2012;Nour et al, 2017Nour et al, , 2015aNour et al, and 2015b and even as aquaculture live food (Abdel Rahman et al, 2008 and2010;and El-Wazzan et al, 2009), or as aquaculture powder (Heneash et al, 2016) or as a source of biodiesel (Ashour et al, 2019;Ashour, 2015).…”
Section: Keys Of Microalgae Productionmentioning
confidence: 99%
“…The production of microalgae as live food in marine hatcheries are represent in more than half of the total production costs of the marine larvae production (Canavate and Fernandes-Dıaz 2001). In the past decades, these problems have promoted many studies on the development of food sources alternative to live microalgae (fresh cultures), such as micro-particulate diets (Amjad and Jones 1992), micro-encapsulated and inert food (Medina-Reyna et al 2005), yeasts (Heneash et al, 2016), microalgae paste (Ashour et al, 2019), and microalgae concentrates preserved by several techniques (Brown and Robert 2002). Among all these alternative food sources, microalgae concentrates, such as paste, presented promising results in the total or partial (mixed diet) substitution of the traditional food source (Nunes et al, 2009).…”
Section: Importance Of Microalgae In Marine Hatcheriesmentioning
confidence: 99%
“…The employment of seaweed extracts as biostimulants in agricultural practices is very ancient, having been in use since early plant breeding [3]. Based on their nutritional values, algal cells (either microalgae or seaweeds) represent a treasury of sources of dyes, proteins, fats, polyunsaturated fatty acids (PUFA), polysaccharides, minerals, and antioxidants, as well as plenty of biological components [5][6][7][8][9]. In addition, seaweeds have important environmental functions, being one of the most important components of marine ecosystems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that the constituents, diversity, and communities of marine algae are affected by variations in environmental parameters and nutrient limitation [65][66][67][68][69][70]. During the last few years, the attention on scientific and commercial interest to biotechnological applications of algae as a sustainable source and global commercial for aquaculture [71][72][73][74][75], biofuel [12,76], extracts [77,78], food supplement, pharmaceuticals, and cosmetics were increased [12].…”
Section: Discussionmentioning
confidence: 99%